Exploring changes in processing speed and intraindividual variability in youth following sports-related concussion. (March 2019) - Green, Stephanie L; Keightley, Michelle L; Lobaugh, Nancy J; Dawson, Deirdre R; Mihailidis, Alex
Background: Concussion represents a growing concern in sports participation for adults and youth alike. Studies exploring the neurocognitive sequelae of concussion, such as speed of processing typically compare mean reaction time scores to a control group. Intraindividual variability measures the consistency of reaction times between trials and has been previously explored in adults post-concussion. Some adult studies show increased variability following injury. Developmentally youth show higher intraindividual variability than adults, which may put them at higher risk of increased intraindividual variability change post-concussion. Exploring intraindividual variability may provide additional insight into fluctuating performance reported following injury. Despite preliminary findings of slowed reaction time in youth, a pre-/post-concussion comparison of intraindividual variability of reaction time has not been explored. Objective: To describe and compare pre- and post-concussion measures of processing speed and intraindividual variability in youth. Methods: A pre-/post-concussion design was used to compare mean reaction time and the coefficient of variation before and after sports-related concussion in 18 youth athletes aged 10–14 years using verbal and nonverbal working memory tasks. Pre-/post-concussion reaction time and coefficient of variation were compared using t-tests. Results: The coefficient of variation for nonverbal working memory was significantly higher following concussion, but no changes in average reaction time were found. Conclusions: Preliminary findings suggest that average response times are unchanged following concussion, but the fluctuation across response times is more variable during a nonverbal working memory task in youth. Increased variability in speed of reaction times could have implications for safe return to sports and reduced academic performance.